Is Unilateral Spatial Neglect Associated With Motor Recovery of the Affected Upper Extremity Poststroke? A Systematic Review. (March 2019) - Doron, Noa; Rand, Debbie
Background and Purpose. Individuals with stroke often present symptoms of multiple domains, such as weakness of the affected upper extremity (UE) and unilateral spatial neglect (USN), which are both associated with poor functional outcome. The aims of this systematic review were to search and review studies that investigated (1) the relationship between USN and affected UE sensorimotor recovery poststroke and (2) the effectiveness of sensorimotor interventions to improve the affected UE in patients with USN. Methods. An electronic search of databases (MEDLINE, EMBASE, CINAHL and Cochrane CENTRAL) was conducted using a combination of the following terms: stroke, USN, and affected UE . Studies meeting the inclusion criteria were rated using a modified version of the Quality Index, and relevant data were extracted. Results. A total of 850 studies were identified, and 14 were included; 13 studies assessed correlations between USN and the affected UE capacity/recovery, and 1 study assessed an intervention to improve the UE of individuals with USN. An association between presence of USN and UE capacity/recovery was found in most studies and USN did not interfere with recovery of the affected UE in the single experimental study. Conclusions. USN is associated with poor UE motor capacity and less UE recovery poststroke. Therefore, these impairments should be considered when planning rehabilitation and discharge. Because USN is a well-researched phenomenon, the lack of studies and insufficient evidence related to UE interventions in individuals with USN was unexpected. These interventions should be developed and researched to improve UE and overall functional outcome poststroke.